PENGARUH KEPEMIMPINAN, KOMUNIKASI, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI - Hardjanti, Tatiek Budi; Rahadhini, MD - (Universitas Slamet Riyadi, 2011)
ABSTRACT The objective of this research is to analyze: (1) leadership influence towards employee performance; (2) communication influence towards employee performance; (3) work motivation influence towards employee performance. The population is amount of 49 in social official, labour and regency transmigration Grobogan in 2009. Sampling methods is sensus. Collecting data technique uses inquiry validity and reliability test. Data is analyzed with multi regression analysis, classic assumption test, t test, F test and coefficient determination by using SPSS program. The result of this research shows: (1) the multi regression equation Y = 6,453 + 0,311 X1 + 0,290 X2 + 0,259 X3; (2) t test of leadership have p value 0,000 < 0,05; communication have p value 0,003 < 0,05; work motivation have p value 0,000 < 0,05, so the conclusion there is the influence of leadership, communication and work motivation significant towards employee performance. (3) coefficient determination (R2) = 0,710, that means contribution of leadership, communication and work motivation that influenced towards employee performance 71%, and the residual is influenced by other variables. The hypothesis that said the influence of leadership, communication and work motivation towards employee performance is proved. Keywords: leadership, communication, work motivation, employee performance.